Variety of Leadership Styles in the Islamic Education Ecosystem of the Archipelago - Muhammad Azamuddin Syahapala; Afiful Ikhwan (Yayasan Rahmat Islamiyah, 2025)
Leadership serves as a determining factor in the success of Islamic educational institutions in Indonesia, which currently face complex challenges due to globalization and intense competition among educational institutions. This research examines various leadership typologies applied in different types of Islamic educational institutions in the Archipelago, ranging from traditional pesantren to modern madrasah, focusing on how charismatic leadership interacts with professional management demands and how local wisdom can be integrated into contemporary leadership practices. The research employs a qualitative approach with library research methods through content analysis of various Islamic educational leadership literature. Research findings reveal four main leadership typologies: charisma-based leadership centered on barakah that still dominates pesantren, collective leadership based on deliberation emphasizing participation, transformative leadership based on empowerment focusing on potential development, and adaptive leadership based on context that remains flexible to change. Historical, cultural, and contextual factors influence the selection of leadership styles in each institution. The novelty of this research lies in its comprehensive approach that integrates dimensions of Archipelago local wisdom, Islamic prophetic values, and contemporary leadership theories into a single analytical framework across various types of Islamic educational institutions. The research recommends a transformative-prophetic leadership model based on local wisdom that combines spiritual strength with professional management systems as an ideal solution for developing Islamic educational institutions that are authentic yet remain competitive in the modern era.